Applications of anthropology : professional anthropology in the twenty-first century - Pink, Sarah (Studies in public and applied anthropology, 2006)
At the beginning of the twenty-first century the demand for anthropological approaches, understandings and methodologies outside academic departments is shifting and changing. Through a series of fascinating case studies of anthropologists' experiences of working with very diverse organizations in the private and public sector this volume examines existing and historical debates about applied anthropology. It explores the relationship between the ""pure and the impure""--Academic and applied anthropology, the question of anthropological identities in new working environments, new appropriate to these contexts, the skills needed by anthropologists working in applied contexts where multidisciplinary work is often undertaken, issues of ethics and responsibility, and how anthropology is perceived from the 'outside'. The volume signifies an encouraging future both for the application of anthropology outside academic departments and for the new generation of anthropologists who might be involved in these developments